A Microfluidic Study of Megakaryocytes Membrane Transport Properties to Water and Dimethyl Sulfoxide at Suprazero and Subzero Temperatures - Tseng, Hsiu-Yang (Mary Ann Liebert, Inc., 2011)
Megakaryocytes (MKs) are the precursor cells of platelets. Cryopreservation of MKs is critical for facilitating research investigations about the biology of this important cell and may help for scaling-up ex-vivo production of platelets from MKs for clinical transfusion. Determining membrane transport properties of MKs to water and cryoprotectant agents (CPAs) is essential for developing optimal conditions for cryopreserving MKs. To obtain these unknown parameters, membrane transport properties of the human UT-7/TPO megakaryocytic cell line were investigated using a microfluidic perfusion system. UT-7/TPO cells were immobilized in a microfluidic system on poly-D-lysine-coated glass substrate and perfused with various hyper-osmotic salt and CPA solutions at suprazero and subzero temperatures. The kinetics of cell volume changes under various extracellular conditions were monitored by a video camera and the information was processed and analyzed using the Kedem–Katchalsky model to determine the membrane transport properties. The osmotically inactive cell volume (V(b)=0.15), the permeability coefficient to water (Lp) at 37°C, 22°C, 12°C, 0°C, −5°C, −10°C, and −20°C, and dimethyl sulfoxide (DMSO; Ps) at 22, 12, 0, −10, −20, as well as associated activation energies of water and DMSO at different temperature regions were obtained. We found that MKs have relatively higher membrane permeability to water (Lp=2.62 μm/min/atm at 22°C) and DMSO (Ps=1.8×10(−3) cm/min at 22°C) than most other common mammalian cell types, such as lymphocytes (Lp=0.46 μm/min/atm at 25°C). This information could suggest a higher optimal cooling rate for MKs cryopreservation. The discontinuity effect was also found on activation energy at 0°C–12°C in the Arrhenius plots of membrane permeability by evaluating the slope of linear regression at each temperature region. This phenomenon may imply the occurrence of cell membrane lipid phase transition.